Hierarchical Core‐Shell N‐Doped Carbon@FeP4‐CoP Arrays as Robust Bifunctional Electrocatalysts for Overall Water Splitting at High Current Density. Issue 12 (20th May 2021) - Yan, Puxuan; Hu, Yan; Shoko, Elvis; Isimjan, Tayirjan Taylor; Tian, Jianniao; Yang, Xiulin
Abstract: Exploring non‐precious metal‐based electrocatalysts at high current density and stability is an urgent issue for sustainable H2 production. Here, hierarchical core‐shell N‐doped carbon encapsulated array‐like FeP4 and CoP active components have been fabricated in situ on the surface of nickel foam (NC@FeP4 ‐CoP/NF) by etching sheet‐like ZIF‐67 arrays, Prussian analog formation, and phosphating in turns. The crystallinity, hierarchical heterostructure, and chemical state have been carefully discussed. Electrochemical studies demonstrate that the catalyst displays excellent electrocatalytic activity and durability in electrochemical oxygen evolution reaction (η20  = 218 mV) and hydrogen evolution reaction (η10  = 116 mV), better than most previously reported bifunctional catalysts. Moreover, the bifunctional catalyst only needs 1.72 and 1.80 V cell voltages at 500 and 1000 mA cm −2 respectively, together with a good catalytic stability at 500 mA cm −2 for 48 h, implying potential commercialization prospects. This excellent electrocatalytic performance is mainly attributed to the distinctive hierarchical structure as well as core‐shell NC encapsulated FeP4 ‐CoP active sites, which can enhance the charge transport rate, inhibit the exfoliation of the active materials, provide a larger active surface area, and facilitate electrolyte diffusion and gas release. Abstract : Hierarchical N‐doped carbon encapsulated array‐like FeP4 and CoP active components on nickel foam are fabricated using metal‐organic frameworks etching conversion approach followed by phosphide treatment. The designed catalyst exhibits an excellent bifunctional electrocatalytic activity and stability for overall water splitting at high current density.